DIABETES IS NOT A DISEASE - Kodarusman, Dikdik (Indonesia Epidemiological Journal, 2024)
Background: Since the centenary of the insulin discovery, our ability to manage diabetic conditions has remained low. What we do is only control blood sugar levels, preventing fatal complications. There has never been a cure for the condition. Methods: This stems from a misinterpretation of Banting et al's insulin discovery It is insulin that treats hyperglycemia. So this condition was thought to be due to the absence or deficiency of insulin. In fact, the cause is the massive release of glucagon. Results: The massive release of glucagon is the body's response to an extensive inflammatory reaction. An inflammatory response that causes discomfort. A response that triggers activation of autophagy mechanism by glucagon. Glucagon not only activates autophagy but also gluconeogenesis. A process that results in the condition of hyperglycemia, diabetes. Conclusion: That is the reason why diabetes does not deserve to be called a disease. Diabetes is a compensatory mechanism that is very likely to be present in every disease and is bound to end. Attempts to inhibit or ignore this process will only lead to new compensations, called complications..